Etiology, Clinical Symptoms, and Risk Factors of Oculomotor Nerve Paralysis - Ruslan, Riswanto; Amir, Suliati P.; Arsal, Muh. Yasin (Newinera Publisher, 2025)
The third cranial nerve, also known as the oculomotor nerve, consists of two main components: the external parasympathetic fibers that innervate the ciliary muscles and the sphincter pupillae, and the deep somatic fibers that control the levator palpebrae superioris and four extraocular muscles. Oculomotor nerve palsy has multiple etiologies and can indicate severe underlying pathology. Damage to this nerve results in characteristic symptoms such as ptosis, diplopia, restricted eye movement, and diminished or absent pupillary light reflex. This study aims to evaluate the clinical characteristics of oculomotor nerve paralysis based on its etiology, age distribution, gender prevalence, and associated risk factors. This study employs a literature review using a narrative review design. Data were collected from various indexed and accredited electronic sources such as Scopus, SINTA, DOAJ, SpringerLink, Cochrane, Biomed, Portal Garuda, Google Scholar, Elsevier/Clinical Key, Gale, PubMed, and other relevant databases. A total of 13 relevant articles were identified for this narrative review. The findings indicate that vascular abnormalities, including microvascular ischemia, aneurysms, and subarachnoid hemorrhages, are the most frequent causes of oculomotor nerve paralysis. The most commonly reported symptoms among affected patients are ptosis and diplopia. The condition is most prevalent in individuals aged 51-60 years, and women are more susceptible to oculomotor nerve paralysis than men. The most frequent cause of oculomotor nerve paralysis is an aneurysm of the posterior communicating artery. This condition predominantly affects individuals aged 51-60 years and is more common in women.